Interface engineering and defect passivation for enhanced hole extraction, ion migration, and optimal charge dynamics in both lead-based and lead-free perovskite solar cells - Muhammad Noman; Abdul Haseeb Hassan Khan; Shayan Tariq Jan (Scientific Reports, 2024)
Abstract The study elucidates the potential benefits of incorporating a BiI3 interfacial layer into perovskite solar cells (PSCs). Using MAPbI3 and MAGeI3 as active layers, complemented by the robust TiO2 and Spiro-OMeTAD as the charge-transport-layers, we employed the SCAPS-1D simulation tool for our investigations. Remarkably, the introduction of the BiI3 layer at the perovskite-HTL interface significantly enhanced hole extraction and effectively passivated defects. This approach minimized charge recombination and ion migration towards opposite electrodes, thus elevating device performance relative to conventional configurations. The efficiency witnessed a rise from 19.28 to 20.30% for MAPbI3 and from 11.90 to 15.57% for MAGeI3. Additionally, MAGeI3 based PSCs saw an improved fill-factor from 50.36 to 62.85%, and a better Jsc from 13.22 to 14.2 mA/cm2, signifying reduced recombination and improved charge extraction. The FF for MAPbI3 based PSCs saw a minor decline, while the Voc slightly ascended from 1.24 to 1.25 V and Jsc from 20.01 to 21.6 mA/cm2. A thorough evaluation of layer thickness, doping, and temperature further highlighted the critical role of the BiI3 layer for both perovskite variants. Our examination of bandgap alignments in devices with the BiI3 interfacial layer also offers valuable understanding into the mechanisms fueling the observed improvements.